Pertencimentos e deslocamentos: dilemas do cotidiano contemporâneo - Prestrelo, Eleonora; Uziel, Anna Paula; Ewald, Ariane; Mancebo, Deise; Elia, Luciano (Estudos e Pesquisas em Psicologia, 2007)
Eleonora Prestrelo, Anna Paula Uziel, Ariane Ewald, Deise Mancebo e Luciano Elia